The Implementation of QR Code Media in Improving Students’ German Reading Comprehension Skills - Nurming Saleh; Syamsurijal Syamsurijal; Nuramalia Nuramalia (Phonologie : Journal of Language and Literature, 2025)
Abstract. This research aims to determine the planning, implementation, and results of reading comprehension skills in the German language students of class XI 8 at SMA Negeri 14 Makassar using QR Code media. This research  is a classroom action research consisting of two cycles. The subjects of this research are 36 students and one German language teacher from class XI 8 at SMA Negeri 14 Makassar. The data of this research consists of two types of data, namely qualitative data obtained from the observations of teachers who inform that students collaborated with the teacher in preparing learning devices and during the learning process, the teacher was able to effectively use QR Code media and actively assisted students who had difficulty understanding the text. Observations from students indicated that they appeared enthusiastic in participating in the learning using QR Code media, so most students were able to understand the reading content and answer the questions provided. The quantitative data were obtained from reading comprehension ability tests of the students. The results of the research showed that the reading comprehension test scores in cycle I were 62.80 and in cycle II were 79. This research indicates that the implementation of QR Code media can improve the reading comprehension skills of students at SMA Negeri 14 Makassar.Keyword: Implementation, Reading Comprehension, QR Code, German Language